Karakteristik Tanah Area Pasca Penambangan Di Desa Tanjung Pauh - Ida Nursanti (Universitas Batanghari, 2018)
The post-mining soil has poor chemical and physical properties and has a very low fertility rate. The objective of this research is to know the land post-mining characteristics related to planting medium. Implementation of research in Tanjung Pauh Village and soil Laboratory. The research was conducted by survey method and soil laboratory test. Data analysis of the diversity of post-mining soil characteristics is presented in table form and discussed descriptively. Post-mine soil chemical and physical characteristic: soil acidity level in very acidic position pH 4, Al saturation of high criterion equal to 52,86%, iron content 1,51% high criterion, Cation Exchange Capacity of 15,21 cmol (+) kg-1 is low, Saturation saturation of 49.44% is moderate, C-organic is very low that is equal to 0.16%, C / N value of soil 1.46 is very low, N total 0, 11%, P available 9,20 mg kg-1 and K total of soil 0,15 mg kg-1 are each classified as low. The post-mining land has poor physical and chemical characteristics of soil as planting medium. Keywords: soil chemistry, physical soil, Post MineABSTRAKTanah pasca penambangan memiliki sifat kimia dan fisik yang kurang baik serta memiliki tingkat kesuburan yang sangat rendah. Penelitian bertujuan mengetahui karakteristik tanah pasca tambang terkait sebagai media tanam. Pelaksanaan penelitian di Desa Tanjung Pauh dan Laboratorium tanah. Penelitian dilaksanakan dengan metode survey dan uji laboratorium tanah. Analisis data keragaman karakteristik jenis tanah pasca penambangan disajikan dalam bentuk tabel dan dibahas secara deskriptif. Karakteristik kimia dan fisik tanah pasca tambang: tingkat kemasaman tanah berada pada posisi sangat masam pH 4, kejenuhan Al kriteria tinggi sebesar 52,86%, kadar besi 1,51% kriteria tinggi, KTK (Kapasitas Tukar Kation) tanah sebesar 15,21 cmol(+)kg -1 tergolong rendah, Kejenuhan Basa (KB) sebesar 49,44% tergolong sedang, C-organik sangat rendah yaitu sebesar 0,16%, Nilai C/N tanah 1,46 tergolong sangat rendah, N total 0,11%, P tersedia 9,20 mg kg-1 dan K total tanah 0,15 mg kg-1 masing-masing tergolong rendah.Tanah pasca penambangan memiliki karakteristik fisik dan kimia tanah yang kurang baik sebagai media tanam.Kata kunci : Kimia tanah, fisik tanah, Pasca Tambang